Energy efficient improved content addressable memory using quantum-dot cellular automata - Kotte, Sujatha; Kanaka Durga, Ganapavarapu (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Quantum-dot cellular automata (QCA) is an emerging technology with high integration density, low power consumption, and high operating speed. This study introduces a QCA-based modified content addressable memory (CAM) cell employing a five-input minority gate. The functionality, temperature sensitivity, and heat distribution of this modified CAM cell are comprehensively analyzed using QCADesigner E and QCA Pro simulation tools. The results reveal significant advancements over existing designs, with a remarkable 8.33% reduction in area and a substantial 63.7% decrease in energy consumption. Additionally, this modified CAM cell exhibits a notable 5% enhancement in temperature tolerance. These findings emphasize the QCA-based modified CAM cell is more efficient and thermally robust.